Peningkatan Keterampilan Membaca dengan Menggunakan Audiovisual Siswa Kelas VI SDN Sindangsari III Kabupaten Tangerang - Zuliani, Rizki; Abwandi, Danar; Firdaus, Muhammad Yaufan (Al-DYAS, 2023)
This research was motivated by low reading skills in class VI at SDN Sindang Sari III, Tangerang Regency. The formulation of the problem is as follows, can the use of audio-visual media improve the reading skills of students at SDN 04 Kemiri. The purpose of this research is to improve reading skills by using audio-visual media. The type of research used is Classroom Action Research (CAR). The research location was in class VI of SDN Sindang Sari III, Tangerang Regency. The research subjects were 22 class II students. Data collection techniques use test techniques and non-test techniques. The research instrument is a test sheet and non-test sheet. The results of research on reading skills using audio-visual media in class VI of SDN Sindang Sari III, Tangerang Regency.